Provision of economic-responsible and analytical-controlling function of asset management instruments - Ryzhakova, G.; Ryzhakov, D.; Shpakova, A.; Pristinskaya, I.; Kondratsky, V.; Fedorova, Y.; Koshelnaya, V.; Maksimyuk, Yu. (Ways to Improve Construction Efficiency, 2018)
The article is devoted to the development of scientific and methodological basis and tools for investment support of housing construction, which is considered in the context of mutual coordination with the specifics of economic and contractual relations of leading subjects of residential development – lender, developer, investors. Methodological developments are based on the existing methodology of project management, the formation of a simplified and complete conceptual model of differentiated attraction of sources of resource support, based on the theory of stakeholders, methods of economic evaluation of sources of financing and attraction of investments and value-oriented goal-setting. The paper analyzes the existing concepts, models, methods of management of investment and construction projects, characterizes the current level of success of such projects. It was found that the housing project management system needs to be improved in terms of shifting the emphasis from maximizing the profit of builders to achieving the value of the project results for all its stakeholders throughout the life cycle of the project. The conceptual model of the problem-targeted differentiated choice of sources of resource support for investment and construction projects in housing construction is proposed.